Dopamine receptors and key elements of the neurotrophins (BDNF, CDNF) expression patterns during critical periods of ontogenesis in the brain structures of mice with autism-like behavior (BTBR) or its absence (С57BL/6J) - P. D. Pravikova; M. A. Arssan; E. A. Zalivina; E. M. Kondaurova; E. A. Kulikova; I. I. Belokopytova; V. S. Naumenko (Вавиловский журнал генетики и селекции)
Analysis of the mechanisms underlying autism spectrum disorder (ASD) is an urgent task due to the everincreasing prevalence of this condition. The study of critical periods of neuroontogenesis is of interest, since the manifestation of ASD is often associated with prenatal disorders of the brain development. One of the currently promising hypotheses postulates a connection between the pathogenesis of ASD and the dysfunction of neurotransmitters and neurotrophins. In this study, we investigated the expression of key dopamine receptors (Drd1, Drd2), brain-derived neurotrophic factor (Bdnf), its receptors (Ntrkb2, Ngfr) and the transcription factor Creb1 that mediates BDNF action, as well as cerebral dopamine neurotrophic factor (Cdnf) during the critical periods of embryogenesis (e14 and e18) and postnatal development (p14, p28, p60) in the hippocampus and frontal cortex of BTBR mice with autism-like behavior compared to the neurotypical C57BL/6 J strain. In BTBR embryos, on the 14th day of prenatal development, an increase in the expression of the Ngfr gene encoding the p75NTR receptor, which may lead to the activation of apoptosis, was found in the hippocampus and frontal cortex. A decrease in the expression of Cdnf, Bdnf and its receptor Ntrkb2, as well as dopamine receptors (Drd1, Drd2) was detected in BTBR mice in the postnatal period of ontogenesis mainly in the frontal cortex, while in the hippocampus of mature mice (p60), only a decrease in the Drd2 mRNA level was revealed. The obtained results suggest that the decrease in the expression levels of CDNF, BDNF-TrkB and dopamine receptors in the frontal cortex in the postnatal period can lead to significant changes in both the morphology of neurons and dopamine neurotransmission in cortical brain structures. At the same time, the increase in p75NTR receptor gene expression observed on the 14th day of embryogenesis, crucial for hippocampus and frontal cortex development, may have direct relevance to the manifestation of early autism.